Thermochemical assessment of the load-bearing capacity of steel-reinforced elastomeric bearings subjected to fire loading. (1st April 2018) - Traxl, R.; Maier, M.; Bauer, S.; Schaur, A.; Zeiml, M.; Lackner, R.
Highlights: Thermochemical characterization of polychloroprene. Model for capturing thermal degradation of polychloroprene. Thermochemical FEM simulation of steel-reinforced elastomer bearings at fire load. Fire experiment on steel-reinforced elastomer bearings for model validation. Numerical study highlighting the influence of geometry, material and load parameters. Abstract: This paper addresses the characterization and analysis of the thermochemical behavior of steel-reinforced elastomer (polychloroprene) bearings during fire loading. Based on results obtained from thermogravimetry (TGA) and differential scanning calorimetry (DSC) experiments, a thermochemical model capturing the effective behavior of the elastomer is proposed. The obtained material model is implemented in a finite element program for evaluating the evolution of temperature and material degradation within steel-reinforced elastomeric bearings commonly employed in engineering practice. In a first step, the analysis tool is applied to the re-analysis of experiments, where sections of a steel-reinforced elastomeric bearing are subjected to a pre-specified temperature load while measuring the temperature increase within the steel and elastomer layers. Measured data and simulation results show good agreement, finally paving the way for the application of the proposed analysis tool to the analysis of the time-dependent heat penetration of steel-reinforced elastomeric bearings in the course of a fire incident. The obtained results provide useful information on the remaining load-bearing capacity of elastomeric bearings finally entering the safety analysis of buildings and bridges supported by these bearings.